Magnetic metal powder, method for producing the same, and sintered magnet
By preparing magnetic powders of Sm and Fe elements in DC plasma equipment, the problem of degradation of magnetization characteristics in ThMn type magnetic alloys in the prior art is solved, and the high thermal stability and magnetization performance are improved, and the use of rare elements is reduced.
Patent Information
- Application Number
- JP2023170579
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
In the conventional ThMn type cone crystal structure magnetic alloy, magnetization characteristics are reduced due to the added phase-stabilizing elements, and it is difficult to produce magnetic powders with high thermal stability and magnetization properties without phase-stabilizing elements.
Magnetic powders are prepared using Sm and Fe elements, and by gasifying and rapidly cooling the master powders of Sm and Fe in DC plasma equipment, magnetic powders containing no or small amounts of phase-stable elements are generated.
Magnetic powder production without adding phase-stable elements is achieved, reducing the use of rare elements, and improving the thermal stability and magnetization performance of magnetic powder.
Smart Images

Figure 2025060076000002 
Figure 2025060076000003 
Figure 2025060076000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic metal powder and a method for producing the same, and also to a sintered magnet body using the magnetic metal powder. [Background technology]
[0002] Nd-Fe-B magnets, currently the strongest magnets in the world, are widely used in hybrid and electric vehicle motors and various energy-saving electrical appliances, but they have a problem with low heat resistance. Therefore, in order to make them usable in temperature environments of 200°C or higher, such as in automotive motor applications, it is necessary to improve the heat resistance of the magnets by adding rare earth elements such as dysprosium (Dy) and terbium (Tb). Since these rare earth elements have been pointed out as posing a risk to the resource supply, there is a need to develop new magnet materials that are rare earth element-free or use reduced amounts of rare earth elements. ThMn 12 The ThMn type alloys have a low content of rare earth elements and are expected to have excellent heat resistance and magnetic properties, and are attracting attention as magnetic materials to replace Nd-Fe-B magnets. 12 The structural instability of the die alloy was an issue.
[0003] To date, the structure of the stabilized ThMn 12 For example, Non-Patent Document 1 describes ThMn alloys to which phase stabilizing elements such as molybdenum (Mo), tantalum (Ta), niobium (Nb), tungsten (W), titanium (Ti), vanadium (V), chromium (Cr) or silicon (Si) have been added. 12 Type alloy RFe 12-x M x is stated. In addition, Non-Patent Document 2 describes a phase-stabilizing element, cobalt (Co), added to ThMn 12 Type alloy Sm(Fe 1-x Co x ) 12 A thin film comprising: [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] GCHadjipanayis et al.Engineering,6,2020,141-147 [Non-Patent Document 2] YKTakahashi et al,J.Jpn.Soc.Powder Matallurgy,69,2022,S74-S83 Summary of the Invention [Problem to be solved by the invention]
[0005] ThMn described in Non-Patent Documents 1 and 2 12 However, the problem with the type alloys was that the magnetic properties were degraded due to the presence of phase stabilizing elements. In addition, in order to manufacture bulk magnets, it was necessary to obtain the magnetic material in the form of powder, not as a thin film as described in Non-Patent Document 2. Therefore, an object of the present invention is to provide a novel magnetic metal powder that does not require the addition of a phase stabilizing element and that allows the amount of rare earth elements used to be reduced. [Means for solving the problem]
[0006] The present invention provides a magnetic metal powder that contains samarium (Sm) and iron (Fe) elements and has a peak in the 2θ value range of 35.0° or more and 36.8° or less in an X-ray diffraction pattern measured by an X-ray diffractometer using CuKα1 radiation.
[0007] The present invention also provides a method for producing magnetic metal powder, which includes the steps of supplying first mother powder containing metallic samarium (Sm) and second mother powder containing metallic iron (Fe) into a laminar plasma frame generated in a chamber, gasifying both mother powders in the plasma frame, and rapidly cooling particles produced from both mother powders to produce magnetic metal powder. Effect of the Invention
[0008] The present invention provides a novel magnetic metal powder that does not require the addition of a phase stabilizing element and uses a reduced amount of rare earth elements. A magnet body produced using the magnetic metal powder is expected to have excellent heat resistance and magnetization properties. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic diagram showing an example of a DC plasma device for producing the magnetic metal powder of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view that typically shows a cross section of the DC plasma device shown in FIG. 1, perpendicular to the ejection direction of the plasma flame. [Diagram 3] FIG. 3 is an X-ray diffraction pattern of the magnetic metal powder of Example 1. [Figure 4] FIG. 4 is an X-ray diffraction pattern of the magnetic metal powder of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described below based on its preferred embodiments. The magnetic metal powder of the present invention is composed of an aggregate of magnetic metal particles containing samarium (Sm) and iron (Fe). In the following description, the term "magnetic metal powder" may refer to the magnetic metal powder itself or the magnetic metal particles that constitute the magnetic metal powder, depending on the context. As shown in the examples described below, the magnetic metal powder of the present invention is a magnetic metal powder of ThMn 12 The magnetic metal powder of the present invention has an X-ray diffraction pattern similar to that of a known compound having a ThMn structure. 12 SmFe with type structure 12 The magnetic metal powder of the present invention is assumed to include SmFe alloys. 12 The compound suspected to be an alloy is referred to as "Compound A."
[0011] The characteristic peaks contained in the X-ray diffraction pattern of the magnetic metal powder of the present invention are described below. In the X-ray diffraction pattern measured by an X-ray diffractometer using CuKα1 radiation, the magnetic metal powder of the present invention has a peak in the 2θ value range of 35.0° to 36.8°, preferably 35.5° to 36.7°, and more preferably 36.0° to 36.6°. In this specification, "having a peak in the 2θ value range of 35.0° to 36.8°" means that there is a peak whose peak top 2θ value is in the range of 35.0° to 36.8°. The observation of such a peak means that the magnetic metal powder contains compound A, and therefore the magnetic metal powder in which this peak is observed is expected to have excellent heat resistance and magnetization properties.
[0012] In addition to the above peaks, the magnetic metal powder of the present invention preferably has a peak in the X-ray diffraction pattern with a 2θ value in the range of 29.3° or more and 30.5° or less. The magnetic metal powder of the present invention also preferably has a peak in the X-ray diffraction pattern in a 2θ value range of 42.0° or more and 43.0° or less. The magnetic metal powder of the present invention also preferably has a peak in the X-ray diffraction pattern in a range of 2θ values of 47.0° or more and 48.5° or less. The magnetic metal powder may have a peak in one of the above-mentioned ranges, or may have peaks in any combination of two or more of the above-mentioned ranges. The observation of such a peak means that the magnetic metal powder contains compound A, and therefore the magnetic metal powder in which the peak is observed is expected to have excellent heat resistance and magnetization properties.
[0013] As mentioned above, the conventional ThMn 12In the case of the type alloy, the alloy is stabilized by containing a phase stabilizing element, but this causes a problem of a decrease in magnetic properties. Therefore, from the viewpoint of improving magnetic properties, it is preferable that the magnetic metal powder of the present invention does not substantially contain a phase stabilizing element. Examples of the phase stabilizing element include those that have been conventionally used in the technical field. Examples of such elements include titanium (Ti), cobalt (Co), vanadium (V) and zirconium (Zr). Note that "substantially does not contain" means to exclude intentional addition of a phase stabilizing element, and means to allow the inevitable mixing of a small amount of a phase stabilizing element during the manufacturing process of the magnetic metal powder. In other words, it is preferable that the metal elements contained in the magnetic metal powder of the present invention are Sm, Fe and impurity metal elements.
[0014] However, the magnetic metal powder may contain a phase stabilizing element within a range in which high magnetic properties can be obtained. When the magnetic metal powder contains a phase stabilizing element, from the viewpoint of achieving both the structural stability and magnetic properties of the magnetic metal powder, the magnetic metal powder preferably contains a total of 0.010% to 20% by mass of the phase stabilizing element, more preferably 1% to 12% by mass, and even more preferably 2% to 6% by mass.
[0015] From the viewpoint of improving the magnetic properties of a magnet body produced using the magnetic metal powder, it is preferable that the magnetic metal powder contains a high content of compound A. Since it is difficult to directly measure the content of compound A, in the present invention, the content of compound A is estimated using the peak intensity ratio between a peak derived from compound A and a peak derived from a compound other than compound A, which are observed in the X-ray diffraction pattern of the magnetic metal powder. In detail, in an X-ray diffraction pattern measured by an X-ray diffractometer using CuKα1 radiation, The peak intensity of the peak observed in the 2θ value range of 35.0° to 36.8° is defined as I1. The peak intensity of the peak observed in the 2θ value range of 44.2° to 45.1° is defined as I2. The peak intensity of the peak observed in the 2θ value range of 40.0° to 40.9° is designated as I3. The peak intensity of the peak observed in the 2θ value range of 30.5° to 31.2° is designated as I4. When the peak intensity of the peak observed in the 2θ value range of 27.7° to 28.2° is defined as I5, (I2+I3+I4+I5) / I1 is preferably equal to or less than 25, more preferably equal to or less than 23, and even more preferably equal to or less than 21. In addition, (I2+I3+I4+I5) / I1 is ideally 0 (zero). In this specification, the term "peak intensity" refers to the height of a peak.
[0016] In addition, when there are multiple peaks observed in the 2θ value range of 35.0° to 36.8°, the peak intensity of the peak with the maximum intensity among those peaks is designated as I1. This also applies to I2, I3, I4, and I5.
[0017] I1 is the peak intensity of the peak derived from compound A. I2, I3, I4 and I5 are the peak intensities of peaks typically observed that are not attributable to compound A. Specifically, I2 is the peak intensity of the peak attributable to Fe. I3 is the peak intensity of the peak due to SmFe2. I4 is the peak intensity of the peak due to Sm2O3. I5 is the peak intensity of the peak due to Sm2O.
[0018] From the viewpoint of achieving a high content of compound A, I2 / I1 is preferably equal to or less than 23, and more preferably equal to or less than 18. Furthermore, I2 / I1 is ideally 0 (zero). From the same viewpoint, I3 / I1 is preferably 1.2 or less, and more preferably 1.0 or less, and ideally I3 / I1 is 0 (zero). From the same viewpoint, I4 / I1 is preferably 0.80 or less, and more preferably 0.56 or less, and ideally I4 / I1 is 0 (zero). From the same viewpoint, I5 / I1 is preferably 8.0 or less, and more preferably 7.0 or less, and ideally I5 / I1 is 0 (zero).
[0019] The magnetic metal powder of the present invention has a volume cumulative particle size D at 50% cumulative volume as observed by a scanning electron microscope. SEM50 It is preferable that the diameter of the particles is 0.20 μm or more and 0.72 μm or less. SEM50 represents the particle size of the primary particles. D of magnetic metal powder SEM50 By setting the particle size to be 0.20 μm or more and 0.72 μm or less, the magnetization characteristics of the magnetic metal powder can be controlled within a more preferable range. In order to further enhance such effects, the magnetic metal powder of the present invention has a D SEM50 is more preferably 0.64 μm or less, and further preferably 0.55 μm or less. SEM50 It is more preferable that the thickness is 0.25 μm or more, and further preferably 0.30 μm or more. In this specification, a primary particle refers to an object that can be recognized as the smallest unit of a particle, judging from its apparent geometric shape.
[0020] D SEM50 The definition of is as follows: From the scanning electron microscope image of the magnetic metal powder, 1000 magnetic metal particles that do not overlap each other are randomly selected to measure the particle size (Heywood diameter). Next, from the obtained particle size, the volume of the particle is calculated assuming that it is a sphere, and the volume cumulative particle size at 50% of the cumulative volume is defined as D. SEM50 It is defined as:
[0021] In addition to being fine, the magnetic metal powder of the present invention is preferably also highly dispersible. A fine and highly dispersible magnetic metal powder exhibits good packing properties, has high saturation magnetization, and makes it easy to improve the magnetization characteristics. From these viewpoints, the volume cumulative particle size at 50% cumulative volume measured by the laser diffraction scattering particle size distribution measurement method is defined as D LDS50 Then, D LDS50 / D SEM50 The value of is preferably 4.2 or less, and more preferably 4.0 or less. LDS50 / D SEM50 Theoretically, the lower limit is 1, but 1.2 is more realistic. When the magnetic metal powder of the present invention has such a particle size distribution, the degree of aggregation between the particles constituting the powder is low and the proportion of primary particles is high. Magnetic metal powders having such a particle size distribution are preferably produced, for example, by the production method described below.
[0022] From the viewpoint of suppressing aggregation between primary particles, the D LDS50 The magnetic metal powder of the present invention is preferably 0.64 μm or more, more preferably 1.0 μm or more, and even more preferably 1.2 μm or more. In addition, when the magnetic metal powder of the present invention is used as a material for a power inductor, from the viewpoint of making it difficult for an eddy current to occur, its D LDS50 The value is preferably 2.9 μm or less, more preferably 2.6 μm or less, and even more preferably 2.4 μm or less.
[0023] D LDS50 The measurement can be carried out, for example, by the following method. That is, 0.1 g of a measurement sample is mixed with 50 mL of water and dispersed for 1 minute using an ultrasonic homogenizer (US-300T, manufactured by Nippon Seiki Seisakusho). Then, the particle size distribution is measured using a laser diffraction scattering type particle size distribution measuring device, for example, MT3300 EXII, manufactured by Microtrack Bell.
[0024] In order to control the magnetic properties of the magnetic metal powder within a more preferable range, the BET specific surface area of the magnetic metal powder is set to 2.8 m 2 / g or more is preferable, and 3.0m 2 / g or more is more preferable, and 3.2m 2 / g or more is more preferable, and 3.3m 2 / g or more is particularly preferred. In order to improve the green density of the magnetic metal powder and to obtain excellent magnetic properties, the BET specific surface area of the magnetic metal powder is set to 4.8 m. 2 / g or less is preferable, and 4.6m 2 / g or less is more preferable, and 4.4m 2 / g or less is more preferable, and 4.3m 2 / g or less is particularly preferred. The BET specific surface area can be measured, for example, using a nitrogen-helium mixed gas containing 30 volume % of nitrogen as an adsorption gas and 70 volume % of helium as a carrier gas, and a BET specific surface area measuring device (HM model-1210, manufactured by Mountec Co., Ltd.), in accordance with "(3.5) One-point method" under "6.2 Flow method" in JIS R 1626 "Gas adsorption of fine ceramic powders - Measurement method of specific surface area by the BET method."
[0025] The magnetic metal particles constituting the magnetic metal powder may be composed of a single layer or multiple layers. An example of a magnetic metal particle composed of multiple layers is a magnetic metal particle having a core portion and a shell portion disposed on the surface of the core portion.
[0026] There is no particular limitation on the shape of the particles constituting the magnetic metal powder, and various shapes can be adopted, such as, for example, spherical, flake, polyhedral, etc. From the viewpoint of improving the packing property of the magnetic metal powder and increasing the saturation magnetization, the shape of the magnetic metal particles is preferably spherical. The term "spherical" means that the circularity coefficient measured by the following method is preferably 0.85 or more, and more preferably 0.90 or more. The circularity coefficient is calculated by the following method. A scanning electron microscope image of the magnetic metal powder is taken, and 1000 magnetic metal particles that do not overlap are randomly selected. When the area of the two-dimensional projected image of the metal particle is S and the perimeter is L, the circularity coefficient of the particle is calculated as 4πS / L. 2 The circularity coefficient is calculated from the formula. The arithmetic average value of the circularity coefficients of each magnetic metal particle is taken as the circularity coefficient mentioned above. When the two-dimensional projected image of a magnetic metal particle is a perfect circle, the circularity coefficient of the particle is 1.
[0027] Next, a preferred method for producing the magnetic metal powder of the present invention will be described. In this method, a first mother powder containing metallic samarium (Sm) and a second mother powder containing metallic iron (Fe) are subjected to a direct current thermal plasma (hereinafter also referred to as "DC plasma") method to generate magnetic metal powder from the mother powder. In detail, this method includes a step of supplying the first mother powder and the second mother powder into a plasma frame in a laminar flow state generated in a chamber, gasifying both mother powders in the plasma frame, and quenching the particles generated from both mother powders to generate magnetic metal powder. When the magnetic metal powder does not contain a phase stabilizing element, it is preferable that the first mother powder is made of metallic Sm and unavoidable impurities. Also, it is preferable that the second mother powder is made of metallic Fe and unavoidable impurities. When the magnetic metal powder contains a phase stabilizing element, it is sufficient to include the phase stabilizing element in at least one of the first mother powder and the second mother powder described above.
[0028] A DC plasma device suitable for use in this manufacturing method is shown in Fig. 1. As shown in the figure, the DC plasma device 1 includes a powder supplying device 2, a chamber 3, a DC plasma torch 4, a collection pot 5, a powder supplying nozzle 6, a gas supplying device 7, a pressure adjusting device 8, and a cooling gas nozzle 9. In this device, the base powder passes through the inside of the DC plasma torch 4 from the powder supplying device 2 through the powder supplying nozzle 6. A gas for generating thermal plasma (hereinafter also referred to as "plasma gas") is supplied to the plasma torch 4 from the gas supplying device 7 to generate a plasma flame 10. In addition, the base powder is gasified in the plasma flame 10 generated by the DC plasma torch 4 and released into the chamber 3, after which the particles generated from the base powder are rapidly cooled and become fine particles of magnetic metal particles 11, which are accumulated and collected in the collection pot 5.
[0029] Compound A not containing a phase stabilizing element is unstable and has been difficult to produce in the past. However, the present inventors have found that compound A can be successfully produced by rapidly cooling particles produced from mother powder. In particular, from the viewpoint of increasing the proportion of compound A contained in the magnetic metal powder, the cooling rate of the particles produced from the mother powder is preferably 10 5 K / sec or more.
[0030] As described above, the DC plasma device 1 has a plurality of cooling gas outlets 9. By blowing the cooling gas from the cooling gas outlets 9 toward the plasma flame 10, the plasma flame 10 containing the particles generated from the mother powder can be rapidly cooled. As shown in FIG. 2, the DC plasma device 1 has a plurality of cooling gas outlets 9. This allows the cooling gas to be ejected from a plurality of positions and blown toward the plasma flame 10, so that the plasma flame 10 can be cooled more effectively. In this case, by arranging the plurality of cooling gas outlets 9 at equal intervals along the circumferential direction of the cross section of the chamber 3 and setting the ejection positions of adjacent cooling gases at equal intervals so as to surround the plasma flame 10, it is possible to suppress the uneven cooling that occurs when cooling the plasma flame 10, and therefore a more homogeneous magnetic metal powder can be obtained. From the viewpoint of making this advantage even more prominent, it is preferable to set the direction of the cooling gas outlets 9 in the DC plasma device 1 so that the cooling gas can be blown along a direction perpendicular to the ejection direction of the plasma flame 10.
[0031] As described above, the DC plasma device 1 has multiple cooling gas outlets 9, but instead, the DC plasma device 1 may have only one cooling gas outlet 9, or may not have any cooling gas outlet 9. Even if the DC plasma device does not have a cooling gas outlet 9, the particles generated from the mother powder can be rapidly cooled at the above-mentioned cooling rate as long as there is a sufficient temperature difference between the temperature of the plasma flame 10 and the temperature of the surroundings. The cooling gas to be ejected from the cooling gas ejection port 9 may be, for example, the same kind of gas as the plasma gas.
[0032] From the viewpoint of supplying sufficient energy to the first and second mother powders in the plasma flame 10 and successfully forming fine particles of a desired particle size, it is preferable to adjust the plasma flame 10 so that it is thick and long in a laminar flow state. Whether the plasma flame 10 is in a laminar flow state can be determined by whether the aspect ratio of the frame length to the frame width (hereinafter, frame aspect ratio) is 3 or more when the plasma flame 10 is observed from the side where the frame width is observed to be the widest. Specifically, if the frame aspect ratio is 3 or more, it can be determined to be in a laminar flow state, and if it is less than 3, it can be determined to be in a turbulent flow state.
[0033] In order to make the plasma flame 10 thick and long in a laminar flow state, it is advantageous to adjust the plasma output and plasma gas flow rate. In particular, the plasma output of the DC plasma device 1 is preferably 2.0 kW or more and 100 kW or less, more preferably 2.0 kW or more and 40 kW or less. The flow rate of the plasma gas is preferably 0.10 L / min or more and 25 L / min or less, more preferably 0.5 L / min or more and 21 L / min or less. As the plasma gas, reducing gas such as hydrogen gas, or inert gas such as nitrogen gas and argon gas is preferable.
[0034] From the viewpoint of supplying sufficient thermal energy to the first and second mother powders in the plasma flame 10 to successfully form fine particles of the desired particle size, as well as from the viewpoint of making it difficult for the coarse first and second mother powders to remain, the ratio of plasma output to the supply amount of the first and second mother powders is preferably 0.010 kW·min / g or more and 20 kW·min / g or less, and more preferably 0.050 kW·min / g or more and 15 kW·min / g or less.
[0035] Furthermore, from the viewpoint of stably maintaining the plasma flame 10 in a laminar flow state while reliably obtaining the flow rate required for gasifying the first and second mother powders, the ratio of the plasma gas flow rate to the plasma output (unit: L / (min·kW)) is set to preferably 0.15 or more and 2.0 or less, more preferably 0.40 or more and 1.7 or less, and even more preferably 0.60 or more and 1.5 or less, while maintaining the plasma output and gas flow rate within the above-mentioned ranges.
[0036] When magnetic metal particles are obtained by the DC plasma method, it has been found that it is more advantageous to make the chamber in a low vacuum state than in a high vacuum state, since the cooling rate of the gasified mother powder increases, and as a result, the content of compound A in the magnetic metal particles increases. Specifically, the pressure in the chamber is preferably set to -0.010 kPa or more and -90 kPa or less, expressed as a gauge pressure, more preferably set to -0.50 kPa or more and -60 kPa or less, and even more preferably set to -1.0 kPa or more and -25 kPa or less. By setting the pressure in the chamber within the above range, the generation of SmFe2 can be particularly suppressed.
[0037] When producing a magnetic metal powder containing compound A using the DC plasma device 1 shown in FIG. 1, the particle size D of the base powder is set to 100 nm from the viewpoint of plasma sprayability of the base powder and cost. LDS50 is preferably 3.0 μm or more and 80 μm or less, more preferably 4.0 μm or more and 40 μm or less, in both the first mother powder and the second mother powder, respectively. LDS50 The measurement of the D of the magnetic metal powder mentioned above LDS50 This can be done in a similar manner to the measurement of
[0038] From the viewpoint of the production efficiency of the obtained magnetic metal powder, the supply amount of the mother powder, expressed as the total amount of the first mother powder and the second mother powder, is preferably 5.0 g / min or more and 100 g / min or less, and more preferably 10 g / min or more and 60 g / min or less.
[0039] The ratio of the second mother powder to the total amount of the first mother powder and the second mother powder supplied to the DC plasma device 1 can be set to preferably 66% by mass or more and 80% by mass or less, more preferably 67% by mass or more and 75% by mass or less, and even more preferably 68% by mass or more and 70% by mass or less. By setting the ratio of the second mother powder to the total amount of the first mother powder and the second mother powder within the above range, the ratio of compound A contained in the magnetic metal powder can be further increased.
[0040] The shape of the mother powder is not particularly limited in either the first mother powder or the second mother powder, and examples thereof include dendritic, rod-like, flake-like, cubic, spherical, etc. From the viewpoint of stabilizing the supply efficiency to the plasma torch, it is preferable to use spherical mother powder.
[0041] The magnetic metal particles thus obtained tend to be spherical in shape. The magnetic metal particles are preferably used as a raw material for a sintered magnet body in the form of an aggregate of magnetic metal powder. The sintered magnet body is preferably used, for example, as a core material for a power inductor. On the other hand, the metal powder as an aggregate of metal particles can be used in the form of a magnetic paste by adding a binder or vehicle. The above-mentioned metal powder or magnetic paste can also be compressed and molded into a powder magnetic core. Furthermore, the paste can be molded into a predetermined shape, dried, and solidified to form a solidified molded body, which can be used as a core material for a power inductor.
[0042] The above-described embodiment of the present invention encompasses the following technical ideas. [1] Contains samarium (Sm) and iron (Fe), A magnetic metal powder having a peak in the 2θ value range of 35.0° or more and 36.8° or less in an X-ray diffraction pattern measured by an X-ray diffractometer using CuKα1 radiation. [2] In the X-ray diffraction pattern, The peak intensity of the peak observed in the 2θ value range of 35.0° to 36.8° is defined as I1. The peak intensity of the peak observed in the 2θ value range of 44.2° to 45.1° is defined as I2. The peak intensity of the peak observed in the 2θ value range of 40.0° to 40.9° is designated as I3. The peak intensity of the peak observed in the 2θ value range of 30.5° to 31.2° is designated as I4. When the peak intensity of the peak observed in the 2θ value range of 27.7° to 28.2° is defined as I5, The magnetic metal powder according to [1], wherein (I2+I3+I4+I5) / I1 is 25 or less. [3] Volume cumulative particle size D at 50% cumulative volume measured by laser diffraction scattering particle size distribution measurement method LDS50 The magnetic metal powder according to [1] or [2], wherein the particle size is 0.64 μm or more and 2.9 μm or less. [4] The magnetic metal powder according to any one of [1] to [3], containing titanium (Ti), cobalt (Co), vanadium (V) and zirconium (Zr) in a total amount of 0.01% by mass or more and 20% by mass or less. [5] A sintered magnet body obtained by sintering the magnetic metal powder according to any one of [1] to [4]. [6] A method for producing a magnetic metal powder, comprising the steps of supplying a first mother powder containing metallic samarium (Sm) and a second mother powder containing metallic iron (Fe) into a laminar plasma frame generated in a chamber, gasifying both mother powders in the plasma frame, and quenching particles produced from both mother powders to produce a magnetic metal powder. [7] 10 5 The manufacturing method according to [6], wherein the cooling rate is quenched at a rate of 100 K / sec or more. [8] The manufacturing method according to [6] or [7], further comprising blowing a cooling gas toward the plasma flame in a direction perpendicular to the jetting direction of the plasma flame to rapidly cool the plasma flame. [9] The manufacturing method described in [8], in which the cooling gas is ejected from a plurality of positions and sprayed toward the plasma flame.
[10] The manufacturing method according to [9], wherein the cooling gas is ejected from adjacent ejection positions set at equal intervals so as to surround the plasma flame. EXAMPLES
[0043] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to such examples. Unless otherwise specified, "%" means "% by mass".
[0044] Example 1 Using the DC plasma device 1 shown in Figs. 1 and 2, magnetic metal powder was produced as follows. The first mother powder was Sm powder (particle size D LDS50 The second mother powder was Fe powder (particle size D LDS50 :8μm, spherical) was used. The ratio of the second mother powder, i.e. (amount of second mother powder used) / (amount of first mother powder used + amount of second mother powder used) was 69% (molar ratio Sm:Fe=1:6). The mixed mother powder obtained by mixing both mother powders was supplied to the device 1. The supply amount was set to 20g / min, and the mixed mother powder was supplied to the DC plasma torch 4 through the powder supply nozzle 6 for 5 minutes. Argon (Ar) gas was used as the plasma gas. The flow rate of the plasma gas was set to 16L / min. In addition, the plasma output was set to 15kW. The generated plasma flame was photographed from the side where the frame width was observed to be the widest, and the image was binarized to measure the frame aspect ratio, which is the ratio of the frame length to the frame width. As a result, the frame aspect ratio was 6, and it was confirmed that the plasma flame was a laminar flow. The gauge pressure in the chamber was set to -20kPa.
[0045] [Examples 2 to 5 and Comparative Example 1] A magnetic metal powder was obtained in the same manner as in Example 1, except that the production conditions for the magnetic metal powder were changed as shown in Table 1. A mixed gas of argon and hydrogen (containing 1 volume % hydrogen gas) was used as the plasma gas in Example 5. In Comparative Example 1, the pressure in the chamber was set to -50 kPa, and therefore the particles generated from the mother powder in the plasma flame were not rapidly cooled.
[0046] 〔evaluation〕 (BET specific surface area, D SEM50 and D. LDS50 Measurement of According to the above-mentioned measurement method, the BET specific surface area, D SEM50 and D. LDS50 The results are shown in Table 1.
[0047] (X-ray diffraction pattern measurement) The X-ray diffraction patterns of the magnetic metal powders obtained in each of the Examples and Comparative Examples were measured using an X-ray diffractometer (Rigaku Corporation, RINT-TTRIII) using CuKα ray. The measurements were performed using CuKα ray in a measurement range (2θ: 20° to 50°), with a sampling width of 0.01° and a scan speed of 5° / min. From the obtained X-ray diffraction pattern, the presence or absence of peaks observed in the range of 2θ values of 35.0° to 36.8°, 29.3° to 30.5°, 42.0° to 43.0°, or 47.0° to 48.5° was confirmed. In addition, I1 to I5 were measured, and (I2+I3+I4+I5) / I1, I2 / I1, I3 / I1, I4 / I1, and I5 / I1 were calculated. These results are shown in Table 1. In addition, since no peaks were observed in the range of 35.0° or more and 36.8° or less for Comparative Example 1, "-" was entered in the columns for (I2+I3+I4+I5) / I1, I2 / I1, I3 / I1, I4 / I1, and I5 / I1 in Table 1.
[0048] The X-ray diffraction patterns of Example 1 and Comparative Example 1 are shown in Figures 3 and 4. 11 The X-ray diffraction pattern of V has peaks at 2θ=30.1°, 33.3°, 36.9°, 42.8°, 43.6°, and 47.9°.
[0049] [Table 1]
[0050] As shown in FIG. 3, the X-ray diffraction pattern of the magnetic metal powder of Example 1 is ThMn12 SmFe with type structure 11 The X-ray diffraction pattern of the magnetic metal powders of Examples 1 to 5 was similar to that of ThMn 12 SmFe with type structure 12 It is believed to contain alloys. Furthermore, as shown in Table 1, the magnetic metal powders of each Example all had (I2+I3+I4+I5) / I1 of 25 or less, indicating that the content of compound A was high. [Explanation of symbols]
[0051] 1 DC plasma device 2 Powder feeding device 3. Chamber 4 DC Plasma Torch 5. Collection Pot 6 Powder supply nozzle 7 Gas supply equipment 8. Pressure Regulating Device 9 Cooling gas outlet 10 Plasma Flame
Claims
1. Contains the elements samarium (Sm) and iron (Fe), A magnetic metal powder having a peak in the 2θ value range of 35.0° or more and 36.8° or less in an X-ray diffraction pattern measured by an X-ray diffractometer using CuKα1 radiation.
2. In the X-ray diffraction pattern, The peak intensity of the peak observed in the 2θ value range of 35.0° to 36.8° is defined as I 1 year, The peak intensity of the peak observed in the 2θ value range of 44.2° to 45.1° is defined as I 2 year, The peak intensity of the peak observed in the 2θ value range of 40.0° to 40.9° is defined as I 3 year, The peak intensity of the peak observed in the 2θ value range of 30.5° to 31.2° is defined as I 4 year, The peak intensity of the peak observed in the 2θ value range of 27.7° to 28.2° is defined as I 5 When (I 2 +I 3 +I 4 +I 5 ) / I 1 The magnetic metal powder according to claim 1, wherein the Mn content is 25 or less.
3. Volume cumulative particle size D at 50% cumulative volume measured by laser diffraction scattering particle size distribution measurement method LDS50 The magnetic metal powder according to claim 1 or 2, wherein the particle size is 0.64 μm or more and 2.9 μm or less.
4. 3. The magnetic metal powder according to claim 1 or 2, containing titanium (Ti), cobalt (Co), vanadium (V) and zirconium (Zr) in a total amount of 0.010 mass% or more and 20 mass% or less.
5. A sintered magnet body obtained by sintering the magnetic metal powder according to claim 1 or 2.
6. A method for producing magnetic metal powder, comprising the steps of supplying first mother powder containing metallic samarium (Sm) and second mother powder containing metallic iron (Fe) into a laminar plasma frame generated in a chamber, gasifying both mother powders in the plasma frame, and quenching particles produced from both mother powders to produce magnetic metal powder.
7. 10 5 The method according to claim 6, wherein the quenching is performed at a cooling rate of 100 K / sec or more.
8. 8. The method according to claim 6, further comprising the step of blowing a cooling gas toward the plasma flame in a direction perpendicular to the direction in which the plasma flame is ejected, thereby rapidly cooling the plasma flame.
9. The manufacturing method according to claim 8 , wherein the cooling gas is ejected from a plurality of positions and sprayed toward the plasma flame.
10. 10. The manufacturing method according to claim 9, wherein the cooling gas is ejected from adjacent ejection positions set at equal intervals so as to surround the plasma flame.